The Effect of Subchondral Claw-Deploying Lag Screw on Lateral Sliding Distance and Cut-Out in Treating Intertrochanteric Fractures - Mehmet Cakmak; Levent Horoz (Genel Tıp Dergisi)
Introduction: The incidence of intertrochanteric fractures has increased in recent years due to the growing elderly population at risk of hip fractures, primarily attributed to osteoporosis. Among hip fractures, the prevalence of intertrochanteric fractures is progressively rising. Aim: To evaluate clinical and radiological results of the lag screw that deploys the claw in the subchondral area of the femoral head in the treatment of advanced age unstable intertrochanteric fractures. Methods: We retrospectively reviewed patients with intertrochanteric fractures treated with proximal femoral nails between 2019 and 2021. A total of 107 patients were examined under two groups according to the choice of the nail (Interclaw lag screw(n=52), Proximal femoral nail anti-rotation (n=55) used in the treatment. The radiological parameters in the post-operative 1st-day radiographs of the patients were evaluated. The changes in the first month, three, six months, and one-year control radiographs of the patients were evaluated. Changes in tip apex distance and lateral sliding of the lag screw were compared between the two groups. Result: There was no statistically significant difference between the two groups regarding operation time, post-operative femoral neck/shaft angle, post-operative Calcar gap (mm), and tip-apex distance (TAD) (mm). In the last clinical follow-up, the two groups had a statistically significant difference in the femoral neck/shaft angle and TAD change. There was a significant difference in sliding distance between the two groups at the last follow-up. Conclusion: Using a subchondral claw-deploying lag screw is a reliable implant choice in the surgical treatment of geriatric intertrochanteric fractures. The claw mechanism increases fixation strength and restricts the movements of the lag screw in the femoral head.